2021
DOI: 10.1038/s41366-021-00872-9
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and mortality in critically ill COVID-19 patients with respiratory failure

Abstract: Background Patients with obesity are at increased risk of severe COVID-19, requiring mechanical ventilation due to acute respiratory failure. However, conflicting data are obtained for intensive care unit (ICU) mortality. Objective To analyze the relationship between obesity and in-hospital mortality of ICU patients with COVID-19. Subjects/methods Patients admitted to the ICU for COVID-19 acute respiratory distress syndrome (ARDS) were includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
56
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(75 citation statements)
references
References 47 publications
7
56
1
2
Order By: Relevance
“…Interestingly, multifactorial analysis indicated a paradoxical relationship between the category of BMI and mortality. Patients whose BMI was ≤29 kg/m 2 (OR = 3.64) and those whose BMI was >39 kg/m 2 (OR = 10.45) were more at risk of death compared to those with a BMI of 29-39 kg/m 2 [26]. Researchers point out that the risk of a severe COVID-19 disease course and invasive ventilation in the ICU is higher in patients being overweight or with obesity [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, multifactorial analysis indicated a paradoxical relationship between the category of BMI and mortality. Patients whose BMI was ≤29 kg/m 2 (OR = 3.64) and those whose BMI was >39 kg/m 2 (OR = 10.45) were more at risk of death compared to those with a BMI of 29-39 kg/m 2 [26]. Researchers point out that the risk of a severe COVID-19 disease course and invasive ventilation in the ICU is higher in patients being overweight or with obesity [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review of predictors of in-hospital mortality in COVID-19 concluded that obesity was only associated with mortality in studies that included fewer critically-ill patients [24]. However, these studies used ill-specified multivariable models that did not focus on the association between obesity and hospital mortality and used heterogeneous obesity categorizations [14,18,25,[30][31][32]. Thus, the association between obesity, defined as a high body mass index (BMI), and hospital mortality specifically in critical COVID-19 patients is not yet well-defined.…”
Section: Introductionmentioning
confidence: 99%
“…RESULTS: We included 94 patients. Median [q1, q3] body mass index (BMI) was 29 [26][27][28][29][30][31][32] kg/m 2 and 37% of patients were obese (defined as BMI > 30 kg/m 2 ). Hospital mortality for the entire cohort was 33%.…”
mentioning
confidence: 99%
“…The PaO 2 /FIO 2 ratio has been reported as an independent factor related to death in COVID-19 subjects receiving intensive care (22). In addition, obesity has been associated with substantially increased risks of severe outcomes in patients with COVID-19 (23). Therefore, it is perhaps surprising that in the logistic regression models, we found that the obesity was negatively associated with the study outcomes.…”
Section: Discussionmentioning
confidence: 68%
“…This could be due to the J-shaped association between BMI and the mortality curve. It was already reported that survival rates of subjects with moderate obesity were higher than for those with normal body mass index (BMI), overweight or severe obesity subjects (23). However, a clear limitation of our study is that data on BMI were not available and the analyses were only based on a clinical recorded diagnosis of obesity in the clinical records, which is not a solid variable to analyse the contribution of adiposity on the outcomes.…”
Section: Discussionmentioning
confidence: 95%